DAMPAK STRES KERJA PUSTAKAWAN PADA MASA PANDEMI COVID-19 TERHADAP LAYANAN PERPUSTAKAAN PERGURUAN TINGGI - Nur Riani; Nurul Setyawati Handayani (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
Coronavirus Disease 2019 (Covid-19) has been declared as a pandemic. It impacts all sectors including the education field from the elementary to higher education level. The university students have to follow the academic activity online which of course needs information in the process. Therefore, the college library would have to keep performing its services. The services will also apply the standard health protocol and practice the social distancing appeal. Many innovations are conducted so the librarian should be flexible as to follow. Some of them may experience the effect such as becoming uncomfortable, feeling afraid and anxious, or even overstressed. Those would lead to the decreased performance. The aim of this research is to understand how to overcome the effect covid-19 pandemic condition to library service in the university library. Hence, this will help to solve the anxiety issue of the librarians. This research used library research methodology where the supporting data are achieved by understanding the environment and carefully look at the current situation. The result shows that the librarian stress is caused by their own self-perception. Therefore, it is necessary to manage self-control to avoid any difficulties in the future. In this case, the solution from Bill using long and short term methodology can be applied to overcome the work stress.Keywords: work stress, librarian, covid-19, library service